Pengembangan E-Modul Berbasis Etnomatematika untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa SMAN 1 Grobogan - yolanda, dhea; Sugiyanti, Sugiyanti; Prayito, Muhammad (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2023)
This media development research was motivated by the problems experienced by SMAN 1 Grobogan, namely the limited learning resources or teaching materials and the absence of electronic learning media and the low ability to understand students mathematical concepts which only reached 59,33 and the results of the questionnaire showed that 79% of students need electronic learning media. The aims of this study were. (1) to develop an ethnomatematics-based e-module as a learning medium to improve students ability to understand mathematical concepts. (2) test the validity of the ethnomatematics-based e-module to improve students ability to understand mathematical concepts. (3) testing the practicality of ethnomatematics-based e-module to improve students understanding mathematical concepts. Learning media is tool that can be used to assist the learning process, so that it can make it easier for students to receive material from a teacher. Ethnomatematics-based e-module are learning media that contain elements of culture with material on linear equations and inequalities and contain indicators of understanding mathematical concept. The subjects of this study were class X students of SMAN 1 Grobogan, while the research steps used were the ADDIE development model (Analyze, Design, Development, Implementation and Evaluation). Data collection techniques include interviews and questionnaires. Analysis of the data used includes analysis of the process of developing electronic media, analysis of the validation of media experts and material experts, as well as analysis of the practicality of e-modules. The results of the ethnomatematics based e-module validation show very valid criteria with a percentage of 80%. The results of the teacher and student practicality assessment of the ethnomatematics-based e-module show practical criteria with a percentage 71,96%. The test results on evaluating the ability to understand mathematical concepts have experienced a significant increase, reaching 82,94%. Based on the above results, the ethnomatematics-based e-module is suitable for use as a medium for learning mathematics in class X linear equations and inequalities. The results of the research that has been carried out show that the ethnomatematics-based e-module that has been developed has been declared valid, practical and able to improve comprehension skills students mathematical concept. For future research, it is hoped that it will be able to add trigger questions and more types of questions that are not in the book.